IMPLEMENTASI MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS XI F.1 DI SMAN 1 BATANG KAPAS - Putri, Anisyah Pratiwi (Departemen Matematika, 2025)
Education is an important aspect indeveloping quality personnel resources to make the country's life intelligent. Mathematics plays a significant role in knowledge, as stated in Article 37 of Law No. 20 of 2003, which mandates mathematics as a compulsory subject across all education levels. However, current mathematics instruction is still dominated by conventional, teacher-centered models. These methods monotonous and lack active student interaction. Consequently, classroom environments become less engaging, hinder creativity, and fail To fulfill the requirements of 21st-century education, which emphasizes active learning processes. This issue was observed in Grade XI at SMAN 1 Batang Kapas. Students are passive due to teacher dominance.This phenomenon inspired a classroom action research study to carry out the cooperative learning model, Numbered Heads Together (NHT). This model aims to upgrade students' active engagementand learning outcomes, particularly in function composition topics. The study was conducted in two cycles involving Grade XI F.1 students at SMAN 1 Batang Kapas during the 2024/2025 academic year. The results show that the NHT model effectively improved student learning outcomes. This is demonstrated by the average test scores increasing from 82 in Cycle I to 92 in Cycle II, and classical thoroughness rising from 59% in Cycle I to 91% in Cycle II.Keywords– Mathematics, Learning Outcomes, Direct Instruction, Cooperative Learning, NHT